AN ANISOTROPIC CONTINUUMDAMAGE MODEL: THEORY AND NUMERICAL ANALYSES - BRüNIG, MICHAEL (2004)
THE OVERVIEW PAPER DEALS WITH FUNDAMENTAL CONSTITUTIVE ISSUES IN THE ELASTIC-PLASTICDAMAGE RATE THEORY AND NUMERICAL ANALYSES OF THE LARGE STRAIN ELASTIC-PLASTIC DEFORMATION BEHAVIOR OF ANISOTROPICALLY DAMAGED DUCTILE METALS. THE PROPOSED MODEL IS BASED ON A GENERALIZED MACROSCOPIC THEORY WITHIN THE FRAMEWORK OF NONLINEAR CONTINUUM DAMAGE MECHANICS TAKING INTO ACCOUNT KINEMATIC DESCRIPTION OF DAMAGE. IT EMPLOYS THE CONSIDERATION OF DAMAGED AS WELL AS ¯CTITIOUS UNDAMAGED CON¯GURATIONS RELATED VIA METRIC TRANSFORMATIONS. TO BE ABLE TO ADDRESS BOTH THE PLASTIC °OW AND THE ANISOTROPIC DAMAGE PROCESS, RESPECTIVE HELMHOLTZ FREE ENERGY FUNCTIONS OF THE ¯CTITIOUS UNDAMAGED CON¯GURATION AND OF THE CURRENT DAMAGED CON¯GURATION AS WELL AS A GENERALIZED YIELD CONDITION AND A DAMAGE CRITERION ARE INTRODUCED SEPARATELY. THE EVOLUTION LAWS FOR PLASTIC AND DAMAGE STRAINS ARE BASED ON NUMEROUS EXPERIMENTAL OBSERVATIONS AND NUMERICAL CALCULATIONS AT THE MICRO-LEVEL. IDENTI¯CATION OF MATERIAL PARAMETERS IS DISCUSSED IN SOME DETAIL. THE APPLICABILITY OF THE PROPOSED CONTINUUM DAMAGE THEORY IS DEMONSTRATED BY NUMERICAL SIMULATION OF THE INELASTIC DEFORMATION PROCESS OF TENSION SPECIMENS.